PARTISIPASI MASYARAKAT DALAM PROGRAM PENYEDIAAN AIR BERSIH DI DUSUN SUNGAI LILIN - Diana Maulidiyah (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine: 1) availability and need of clean water in Dusun Sungai Lilin, 2) form and level of community participation, and 3) factors that influence the level of community participation in the clean water supply program. This type of research is a Mix Methods research. The study population was the people of Dusun Sungai Lilin using the population of the number of houses. The research sample was RT 06 with 49 houses and RT 07 as many as 42 houses. The data analysis techniques were the 2000 Public Works formula, frequency descriptive, and descriptive analysis. The results showed: 1) availability and need for clean water can be fulfilled in the rainy season and not guaranteed in the dry season, 2) form of community participation at the planning stage in the form of attending meetings 77,5% is very low, submitting suggestions 77,5% is very low, and making decisions 77,5% is very low; construction stage in the form of manpower 77,5% is very low, financing 69,0% is very high, materials 77,5% is very low, thoughts 64,2% is very low, and expertise 77,5% is very low; and the maintenance stage in the form of maintenance 69,0% is very high and responsibility 69,0% is very high. Meanwhile, the level of community participation is at the level of diplomacy, and 3) factors that influence there are supporters and obstacles.